Effect of different solvents on subcritical solvent extraction of oil from Assam tea seeds (Camellia sinensis var. assamica): Optimization of oil extraction and physicochemical analysis - Nontakarn Uoonlue (2019)
© 2018 Wiley Periodicals, Inc. The optimal conditions for extracting oil from Assam tea seeds under subcritical hexane, petroleum ether, and isopropanol conditions to achieve maximum oil yield were investigated for each solvent. The oil yield, physicochemical properties, and stability obtained were compared with those obtained by Soxhlet extraction. Results showed that the optimal conditions for subcritical hexane, petroleum ether, and isopropanol extraction were at temperatures of 75, 75, and 105 °C under pressure of 1,500 psi for 15 min, which gave the highest percentage oil yield of 16.92, 16.27, and 15.05%, respectively. For each solvent, the oil yield obtained by subcritical solvent extraction and Soxhlet extraction methods was not significantly different (p >.05). The extracted oil samples were rich in oleic and linoleic acids. Using subcritical solvent extraction, the oil samples had higher phenolic and beta-carotene content and antioxidant activity and were more stable than those extracted using Soxhlet extraction, and they enhanced the oxidative stability of soybean oil. Practical applications: The subcritical solvent extraction method is a potential technique for extracting oil from Assam tea seeds, providing faster extraction than the Soxhlet method. Assam tea seed oil obtained by the subcritical extraction method has higher antioxidant activity and better stability than that obtained by the Soxhlet extraction method. Additionally, the tea seed oil extracted by both methods had a similar fatty acid composition without significant differences. The main fatty acids of tea seed oil were oleic and linoleic acids. Therefore, the high level of unsaturated fatty acids and good antioxidant activity of tea seed oil make it suitable for use in the food and cosmetic industries.